Making Room for the Other: Maternal Mourning and Eschatological Hope - Thompson, Janice Allison (Modern theology, 2011)
Working with the experiences of mothers, the author explores a two-part thesis: first, that birth-giving and mourning are both works that seek to "make room" for another person; and second, extending the first thesis, that a theology of creation and eschatology can be fruitfully linked by this theme of making room. The author uses the theology of Johann Baptist Metz to explore the contingent nature of living in history, especially by engaging a narrative theological anthropology and an eschatological time-sensitivity, and argues further that the struggle to become human in history depends also on the work of others who make room for us in our struggle.